Advancements in carbon fibre reinforced ultra-refractory ceramic composites: Effect of rare earth oxides addition. (May 2022) - Vinci, Antonio; Silvestroni, Laura; Gilli, Nicola; Zoli, Luca; Sciti, Diletta
Graphical abstract: Highlights: Carbon fibre-reinforced refractory composites produced by slurry infiltration and sintering. Rare Earth Oxides in the matrix enhanced the mechanical properties compared to a REO-free baseline. Lamellar carbides formed during hot pressing improved densification and toughness. Strengths above 600 MPa at 1500 °C and toughness in the 11–17 MPa m½ range were obtained. Abstract: Continuous carbon fibre ceramic matrix composites capable of tolerating multiple thermal-shock cycles and resisting ablation are needed for aerospace and hypersonic systems. Carbon fibre around 50 vol% and ultra-refractory matrices are fundamental parameters. The influence of rare earth (RE) oxides on the microstructure and mechanical properties of carbon fibre-ZrB2 /SiC composites was investigated. Materials were produced by slurry infiltration and hot pressing. The addition of Y2 O3, La2 O3 and CeO2 led to the formation of lamellar boro-carbides that improved the densification, while Sc2 O3 promoted the formation of (Zr, Sc)B2 solid solutions in the matrix. All these composites exhibited improved mechanical properties compared to a RE-free baseline, with room temperature strengths and toughness above 330 MPa and 9 MPa m 0.5, respectively, and strengths above 600 MPa at 1500 °C. The lamellar phase was identified as a fibre by-product with general formula REB2 C2 . Only CeO2 was detrimental on the long run due to its high reactivity with humidity which induced swelling and jeopardized the structural stability of the composite. This study revealed new fundamental insights into the microstructure evolution of carbon-fibre refractory composites and its impact on the mechanical properties, which will contribute to the development of new generation of reusable ceramic matrix composites for harsh environments.